Cytokines, chemokines, and flare in the anterior chamber after femtosecond laser–assisted cataract surgery. Issue 7 (July 2019) - Favuzza, Eleonora; Becatti, Matteo; Gori, Anna Maria; Mencucci, Rita
Abstract : Purpose : To analyze anterior chamber inflammation after pretreatment with a femtosecond laser platform during cataract surgery and compare the results with those of the manual procedure. Setting : Eye Clinic, Department of Surgery and Translational Medicine, University of Florence, Italy. Design : Prospective case series. Methods : Aqueous humor was collected after femtosecond laser pretreatment (femtosecond group) and at the beginning of routine cataract surgery before the primary incision was created (control group). The levels of 14 cytokines and chemokines were measured using a multiplex array system. Surgical parameters (suction time, laser time, effective phacoemulsification time [EPT]) were recorded. Anterior chamber flare was measured by laser photometry preoperatively and 1 day and 7 days postoperatively. Results : Each group comprised 20 eyes. The EPT was significantly lower in the femtosecond group than in the control group. In the femtosecond group, the concentrations of IL (interleukin)‐6, IL‐8, IL‐10, IL‐12, vascular endothelial growth factor, and interferon‐γ were significantly higher than in the control group. Flare in the anterior chamber measured with flare–cell meter was not significantly different between groups at any timepoint. No correlation was found between cytokine concentrations and age in either group and between cytokine levels and suction or laser time and postoperative flare in the femtosecond group. Also, no correlation was found between postoperative aqueous flare and EPT in either group. Conclusions : Despite the rise of proinflammatory cytokines in the aqueous humor after femtosecond laser pretreatment, the anterior chamber flare after cataract surgery was similar to that in controls. This might be a result of the lower EPT required after pretreatment.